Evidence for healing of periodontal defects 5 years after conventional and regenerative therapy: digital subtraction and bone level measurements - Eickholz, Peter; Hausmann, Ernest (Journal of clinical periodontology, 2002)
The aim of the present study was to compare radiographic assessment of bony fill by digital subtraction analyses (DSA) after periodontal surgery of infrabony and furcation defects with bone level measurements.